2012
DOI: 10.1016/j.mcn.2011.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Wild type and P301L mutant Tau promote neuro-inflammation and α-Synuclein accumulation in lentiviral gene delivery models

Abstract: Neurodegeneration involves multiple pathogenic proteins, including Tau, Aβ, TDP-43 and α-Synuclein, but there is little information how these pathogenic proteins interact. We cloned human wild type 4 repeat Tau (Tauwt) and mutant TauP301L into a lentivirus and performed stereotaxic injection into the rat motor cortex to examine Tau modification, neuro-inflammation and changes of other proteins associated with neurodegeneration. TauP301L was associated with more phosphorylation of Tau, including Thr 181 and Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…The current data suggest that amyloid accumulation results in Tau modification (Khandelwal et al, 2010, Rebeck et al, 2010) and protein aggregation similar to over-expression of Tau (Khandelwal et al, 2011a) or Aβ 1–42 (Lonskaya et al, 2012). Accumulation of autophagosomes in neurodegeneration may be due to reduced autophagic flux (Gonzalez-Polo et al, 2005).…”
Section: Discussionmentioning
confidence: 60%
“…The current data suggest that amyloid accumulation results in Tau modification (Khandelwal et al, 2010, Rebeck et al, 2010) and protein aggregation similar to over-expression of Tau (Khandelwal et al, 2011a) or Aβ 1–42 (Lonskaya et al, 2012). Accumulation of autophagosomes in neurodegeneration may be due to reduced autophagic flux (Gonzalez-Polo et al, 2005).…”
Section: Discussionmentioning
confidence: 60%
“…For instance, in rats, αsyn overexpression induced by stereotaxic injection of lentivirus increases phospho-tau levels [94]. On the contrary, rats transduced with tau and mutant P301L tau display an increase of αsyn and phospho-αsyn levels [95]. In another study using adeno-associated vectors for gene transfer into the substantia nigra of rats, overexpression of human wt and P301L tau, but not αsyn, provoked dopaminergic neurodegeneration, reduced striatal dopamine content, and motor deficit as measured by amphetamine-stimulated rotational behavior [96].…”
Section: Tau and α-Synuclein In Vivomodelsmentioning
confidence: 99%
“…Based on immunostaining, the APP23 transgenic mice displayed increased tau phosphorylation and aggregation compared to the wild-type mice also injected with lenti-P301S. Another group found that P301L tau expression caused an increase in tau phosphorylation, tau aggregation, and activated microglia when compared to wild-type tau expression in the rat motor cortex rats [130]. Lentivirus expression of wild-type or P301L tau in the rat HP produced a progressive appearance of dystrophic and fragmented neurites prior to the formation of NFT-like inclusions that developed over 8 months [131].…”
Section: Lentiviral Modelsmentioning
confidence: 99%